Designers' guide to Eurocode 6 : design of masonry structures, EN 1996-1-1 - Morton, John (ICE, 2012)
This guide looks at the provision of the proposed EN 1996 1.1 Eurocode 6 - Design of Masonry Structures. It deals with the key sections in Eurocode 6 and will also clarify which of the informative annexes will be adopted.
Keywords: Masonry -- Standards -- European Union countries.; Structural design -- Standards -- European Union countries.; elektronické knihy; electronic books